2013
DOI: 10.1016/j.ijsu.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The ‘evil twin syndrome’ in chronic pelvic pain: A systematic review of prevalence studies of bladder pain syndrome and endometriosis

Abstract: Almost two thirds of women presenting with CPP have BPS. Large variations in prevalence may be due to variable study selection and quality. Clinicians need to actively investigate patients for BPS, a condition that appears to co-exist with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 13 publications
2
47
0
3
Order By: Relevance
“…Estimates of prevalence of BPS vary. A recent systematic review suggested the prevalence of BPS in women with CPP is as high as 61% [3,4]. Since the exact prevalence in unknown, a range of sample sizes have been calculated based on various levels of prevalence (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of prevalence of BPS vary. A recent systematic review suggested the prevalence of BPS in women with CPP is as high as 61% [3,4]. Since the exact prevalence in unknown, a range of sample sizes have been calculated based on various levels of prevalence (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…1 A systematic review has shown that associated bladder pain syndrome/interstitial cystitis affects around two thirds of women with endometriosis and chronic pelvic pain. 9 Deep infiltrating nodules can have more specific pain symptoms, such as deep dyspareunia, because of their location but there does not seem to be any clear association between the severity of pain reported and the extent or type of disease present. The mechanisms by which endometriosis causes pain are poorly understood but potentially include hormonal stimulation of the deposits, stimulation of neural pathways, inflammation, local bleeding, or a combination of these.…”
Section: Painmentioning
confidence: 99%
“…40,44 However, opioids should be used with caution as there is little evidence they are useful for long-term chronic pain. Early referral to a pain clinic should be considered for patients with refractory symptoms.…”
Section: Evidence Levelmentioning
confidence: 99%